2011
DOI: 10.1111/j.1440-1681.2011.05602.x
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines in inflammation, insulin resistance and cardiovascular disease

Abstract: 1. Obesity is a major determinant of cardiovascular disease (CVD). Studies in the past two decades have shown that adipose tissue is not merely an inert energy reserve of triglycerides, but also an active endocrine organ. 2. Adipose tissue can produce and secrete numerous bioactive peptides and/or proteins termed adipokines. These secretory factors are involved in the regulation of local and systemic inflammation and insulin sensitivity in a paracrine and/or endocrine manner. Inflammation and insulin resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 91 publications
1
57
1
2
Order By: Relevance
“…From previous studies, it is well established that when there is an expansion of adipose tissue, there is a sustained inflammatory response accompanied by adipokine dysregulation, which leads to chronic subclinical inflammation as well as insulin resistance [15]. But the impact of insulin resistance on the effects of adipokines are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…From previous studies, it is well established that when there is an expansion of adipose tissue, there is a sustained inflammatory response accompanied by adipokine dysregulation, which leads to chronic subclinical inflammation as well as insulin resistance [15]. But the impact of insulin resistance on the effects of adipokines are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…LDH release was determined by a lactate dehydrogenase (LDH) release assay using Promega CytoTox-ONE™ kit (Promega) [17]. In brief, 10 4 cells were seeded in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, several studies demonstrated the important role of adiponectin in the regulation of others physiological processes, including lipid metabolism, endothelial function, inflammatory response and cytokine signalling 28 . Dyslipidemia is known as a major risk factor of insulin resistance and MS.…”
Section: Discussionmentioning
confidence: 99%